The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1007/bf03343881
|View full text |Cite
|
Sign up to set email alerts
|

Functional hyperandrogenism detected by corticotropin and GnRH-analogue stimulation tests in women affected by apparently idiopathic hirsutism

Abstract: The etiologic diagnosis of hirsutism is often difficult. Previous studies have reported normal basal androgen and SHBG concentrations in 33-50% of hirsute women, suggesting the presence of an "idiopathic" form of hirsutism as the most frequent cause of this problem. The recent use of GnRH-analogues together with the corticotropin stimulation test allows better understanding of whether the cause of hirsutism is androgen excess and, if so, whether the origin of the latter is ovarian, adrenal or both. The present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 29 publications
0
12
0
1
Order By: Relevance
“…The pathophysiology of IH is presumed to involve a primary increase in skin 5α-reductase activity and possibly an alteration in androgen receptor function [2]. In these patients there may be present mild forms of ovarian and adrenal functional hyperandrogenism [3]. In the light of this information, we investigated whether this peripheral increased androgen activity is associated with insulin metabolism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pathophysiology of IH is presumed to involve a primary increase in skin 5α-reductase activity and possibly an alteration in androgen receptor function [2]. In these patients there may be present mild forms of ovarian and adrenal functional hyperandrogenism [3]. In the light of this information, we investigated whether this peripheral increased androgen activity is associated with insulin metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Idiopathic hirsutism is defined as hirsutism associated with normal ovulatory function and normal circulating serum androgen concentrations [2]. In these patients mild forms of ovarian and adrenal functional hyperandrogenism may be present [3]. Polycystic ovary syndrome (PCOS) is characterized by chronic anovulation, obesity and hyperandrogenism.…”
Section: Introductionmentioning
confidence: 99%
“…This deficiency is due to the fact that most previous studies have included patients in whom the diagnosis of IH was not strictly established. Although IH is thought to be caused by the increased sensitivity of the pilosebaceous unit to the circulating androgens, recently Rossi et al (18) evaluated the adrenal and ovarian function in 48 young hirsute women by using GnRH analog and the ACTH stimulation test. The authors demonstrated that milder forms of functional ovarian and/or adrenal hyperandrogenism, similar to those found in hyperandrogenic women, were observed and could be an underlying mechanism of IH.…”
Section: Discussionmentioning
confidence: 99%
“…Increase in skin 5a-reductase activity [8], hyper-response of pilosebaceous unit to normal levels of circulating androgen [9], or genetic alteration in androgen receptor [10,11] has been postulated as the possible pathogenesis of IH; mild forms of ovarian and adrenal functional hyperandrogenism have been reported in some patients with IH [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%